2004
DOI: 10.1016/j.cub.2004.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Thermosensory and Olfactory Neuron-Specific Genes via Expression Profiling of Single Neuron Types

Abstract: Most C. elegans sensory neuron types consist of a single bilateral pair of neurons, and respond to a unique set of sensory stimuli. Although genes required for the development and function of individual sensory neuron types have been identified in forward genetic screens, these approaches are unlikely to identify genes that when mutated result in subtle or pleiotropic phenotypes. Here, we describe a complementary approach to identify sensory neuron type-specific genes via microarray analysis using RNA from sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 31 publications
6
91
0
1
Order By: Relevance
“…We and others previously showed that the AWB neurons express a subset of predicted GPCRs encoded by the C. elegans genome (Troemel et al 1995;Colosimo et al 2004;Nokes et al 2009;C. Bargmann, personal communication;www.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others previously showed that the AWB neurons express a subset of predicted GPCRs encoded by the C. elegans genome (Troemel et al 1995;Colosimo et al 2004;Nokes et al 2009;C. Bargmann, personal communication;www.…”
Section: Resultsmentioning
confidence: 99%
“…wormbase.org). Of these, str-1 and str-44 are expressed exclusively or primarily in AWB, whereas srsx-3, srd-23, sru-38, srab-16, and str-163 are expressed in AWB as well as in additional chemosensory neurons (Troemel et al 1995;Colosimo et al 2004;Nokes et al 2009;C. Bargmann, personal communication;www.wormbase.org).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in a DYF-5 homologue in Leishmania mexicana, LmxMPK9 (17), and in one of the two homologues in Chlamydomonas reinhardtii, LF4 (18), affect the length of the flagella of these organisms. In addition, several genome-wide approaches have identified DYF-5 and its homologues as likely ciliary proteins (21,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Our understanding of the molecular bases of sensation has benefited substantially from transcriptional analyses of photoreceptors (4), touch receptors (5), thermoreceptors (6), Merkel cells (7), and olfactory neurons (6,8). We have used a functionalgenomics approach to identify genes whose products are involved in the development, maintenance, and function of hair cells in the zebrafish.…”
mentioning
confidence: 99%